Dual-tuning multidimensional superstructures based on a T-shaped molecule: vesicle, helix, membrane and nanofiber-constructed gel. Issue 3 (4th December 2014) - Chu, Xiaoxiao; Xing, Pengyao; Li, Shangyang; Ma, Mingfang; Hao, Jingcheng; Hao, Aiyou
Abstract : Dual-tuning self-assembly of Fmoc–Gly (a T-shape molecule) supramolecular self assembly was firstly reported here. Abstract : As a small molecule, N -(9-fluorenylmethoxy carbonyl)-glycine (FG) possesses a hydrophobic plane domain (π-conjugated section) and a hydrophilic domain (amino acid section), which can be designed into multi-dimensional self-assembly structures under dual tuning. Through controlling the concentration of T-shaped FG, the transformation between various morphologies has been achieved: vesicles are obtained at low concentrations (0.0025–0.005 wt%); helical fibers can be found at the concentration of 0.2 wt% though Gly has no stereocenter, resulting in the birth of chiral organization; fibrous bundles can accumulate into a three dimensional network to finally form a supramolecular gel. Taking gel as an example, we devised a variety of nanostructures including nanoparticles, microparticles, nanoribbons and membranes obtained by adding base. The mechanism of self-assembly formation has been investigated and this system is hoped to enrich the category of nanomaterials from amino acid or short peptides.